2018
DOI: 10.1002/hed.25211
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer involving masticator space (T4b): Review of literature and future directions

Abstract: The oral cancer with masticator-space involvement is classified as T4b disease. The limited data suggest that the masticator space is a complex anatomic area and tumors with varying degrees of infiltration may have different oncologic outcomes. It is not advisable to group all T4b tumors as one and consider them for palliative-intent treatment. A group of patients with limited spread (infra-notch) has potential for good outcome. These cancers can be considered for downstaging to T4a classification based on bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Masticator space invasion is the most common subset of T4b OCSCC compared to disease invasion of the pterygoid plates, skull base, and/or encasement of the internal carotid artery 4 . The masticator space contains the ramus and body of the mandible, the muscles of mastication (medial and lateral pterygoids, masseter and temporalis), and the mandibular nerve 6 . Radical, compartmental, en bloc resection of the entire masticator space contents for improved margin control has been proposed in the Indian population by Trivedi et al This can include en bloc resection of the mandible, maxilla, pterygoid plates, and all of the muscles of mastication from origin to insertion 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masticator space invasion is the most common subset of T4b OCSCC compared to disease invasion of the pterygoid plates, skull base, and/or encasement of the internal carotid artery 4 . The masticator space contains the ramus and body of the mandible, the muscles of mastication (medial and lateral pterygoids, masseter and temporalis), and the mandibular nerve 6 . Radical, compartmental, en bloc resection of the entire masticator space contents for improved margin control has been proposed in the Indian population by Trivedi et al This can include en bloc resection of the mandible, maxilla, pterygoid plates, and all of the muscles of mastication from origin to insertion 7 .…”
Section: Introductionmentioning
confidence: 99%
“…4 The masticator space contains the ramus and body of the mandible, the muscles of mastication (medial and lateral pterygoids, masseter and temporalis), and the mandibular nerve. 6 Radical, compartmental, en bloc resection of the entire masticator space contents for improved margin control has been proposed in the Indian population by Trivedi et al This can include en bloc resection of the mandible, maxilla, pterygoid plates, and all of the muscles of mastication from origin to insertion. 7 Unlike T4b OCSCC invading the pterygoid plates, skull base, and/or encasing the internal carotid artery, masticator space resectability may be more feasible given less morbid constraints on margin clearance (e.g., masseter muscle resection vs. internal carotid artery resection).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it would be difficult to assess tumor invasion if intraoperative bleeding from the pterygoid venous plexus or internal maxillary vessels occurred. [3,4] All these factors contribute to achieving negative margins in T4b OSCC, which is a very arduous process and is presumed to be the major reason why surgical treatment is still not the mainstay treatment for patients with T4b OSCC according to the NCCN guideline. [2] Furthermore, to investigate suitable patients with T4b OSCC who were candidates for primary surgical treatment, Liao et al demonstrated that those patients with T4b OSCC with infranotch tumor involvement who received primary surgical treatment exhibited significantly higher local control, neck control, disease-free survival, and OS rates compared with those with tumor supra-notch spread.…”
Section: Discussionmentioning
confidence: 99%
“…Spread to the MS can be merely due to close anatomical proximity to the tumors involving the posterior part of buccal mucosa. 8 To categorize all tumors involving varying degrees of MS under one prognostic stage is one of the limitations of the current staging system.…”
Section: Discussionmentioning
confidence: 99%